Informed Consent Position in Doctor and Patient Relationship - Inensa Khoirul Harap (Borong Newinera Publisher, 2021)
Awareness of risks may be interpreted as a patient's approval in the context of submitting the doctor's schedule with the necessary details for making an appointment or an informed refuse. Prior to signing the consent document, the agreement, the prospective student already confirmed that she understood the terms and conditions. to let the patient understand anything before doing it, and when making the judgment, the patient should make the most of any of an exhaustive information (informed decision). The kinds of studies found in this paper are what lawyers refer to as